Experimental Transplacental Transmission of St. Louis Encephalitis Virus in Mice - Andersen, A. A. (1970)
Transplacental infection of the mouse embryo with St. Louis encephalitis (SLE) virus was produced by injecting the mother with virus at various stages of gestation. Intravenous or subcutaneous injection of the mother with 10(5.9) suckling mouse median lethal dose (SMLD(50)) of SLE virus was found to infect 83 to 96% of the embryos when given at 4 days of gestation or later. Injections at 6 days of gestation or earlier had little effect on the embryo although virus could be recovered at 10 days of gestation when injected at 4 days of gestation, whereas injections at 7 days or later resulted in a high mortality at birth and during the first week of life. Embryos from females injected at 7 to 9 days of gestation were found to have become infected when necropsied 3 days after injection, but no virus could be isolated from the young of similarly infected mothers at birth. A large number of these young died at birth, and some were observed with signs of anoxia and incoordination. Young of mothers injected later in pregnancy usually lived for a few hours to a few days and were then observed to die with signs of encephalitis. Virus was routinely isolated from these mice.